2020
DOI: 10.1016/j.euo.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Small Primary Tumor Size and Prognosis in Metastatic Renal Cell Carcinoma: Insights from Two Independent Cohorts of Patients Who Underwent Cytoreductive Nephrectomy

Abstract: Background: One of the main challenges in the management of renal cell carcinoma (RCC) is risk-stratifying patients who present with metastatic disease. Tumor size is an important predictor of survival in the localized setting; however, this feature has not been explored fully in patients presenting with M1 RCC.Objective: To assess the impact of tumor size on survival in patients with metastatic RCC who underwent cytoreductive nephrectomy (CN).Design, setting, and participants: We queried the Memorial Sloan Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…The median volume of primary tumors (PV) was 225cm 3 , this was non-normally distributed, with a negative skew (p=0.007). The median total volume of disease (TV) was 236cm 3 , with patients' TV predominantly restricted to the primary tumor (Figure 1). Only three tumors had a volume of metastatic disease (MV) greater than PV, the median percentage of TV resected was 96.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median volume of primary tumors (PV) was 225cm 3 , this was non-normally distributed, with a negative skew (p=0.007). The median total volume of disease (TV) was 236cm 3 , with patients' TV predominantly restricted to the primary tumor (Figure 1). Only three tumors had a volume of metastatic disease (MV) greater than PV, the median percentage of TV resected was 96.7%.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that primary tumor size is an independent predictor of survival following cytoreductive nephrectomy. 3 However, this finding did not consider that tumor volume can vary, even in tumors with identical maximum axial diameter, depending on the shape of disease. 4 Previous studies by Pierorazio et al and Barbastefano et al showed that the fraction of disease resected in a cytoreductive nephrectomy may be significant for survival outcomes, with improved outcomes when a minimum of 90-95% of all disease is debulked.…”
Section: Introductionmentioning
confidence: 92%
“…Translational work suggests that some primary tumors may harbor progressive clones leading to rapid metastasis [13], but CARMENA did not support that CN was beneficial. In addition, due to the size of the tumor, ablation may be an alternative to a surgical approach that may include partial nephrectomy [14][15][16]. In summary, after establishing the diagnosis of the subtype reliably by an RMB, immediate systemic therapy should be preferred in analogy to first-level evidence for ccRCC.…”
Section: 3mentioning
confidence: 99%
“…Patients with a lower tumor burden may have a potential survival benefit by undergoing CN, which could be added to individual decision-making procedures. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, DiNatale et al reported that a primary tumor size ≤ 4 cm was independently associated with improved overall survival (OS) in patients with metastatic clear cell RCC who had undergone surgery earlier. 9 In the present study, we retrospectively examined the data of mRCC patients who had undergo CN retrieved from the database of a Chinese center and the Surveillance, Epidemiology, and End Results (SEER) program and aimed to determine how the size of the primary tumor affects the prognosis of mRCC patients.…”
Section: Introductionmentioning
confidence: 99%